Impact of gamma-ray irradiation on dynamic characteristics of Si and SiC power MOSFETs - Ramani Kannan; Saranya Krishnamurthy; Chay Che Kiong; Taib B Ibrahim (International Journal of Electrical and Computer Engineering (IJECE), 2019)
Power electronic devices in spacecraft and military applications requires high radiation tolerant. The semiconductor devices face the issue of device degradation due to their sensitivity to radiation. Power MOSFET is one of the primary components of these power electronic devices because of its capabilities of fast switching speed and low power consumption. These abilities are challenged by ionizing radiation which damages the devices by inducing charge built-up in the sensitive oxide layer of power MOSFET. Radiations degrade the oxides in a power MOSFET through Total Ionization Dose effect mechanism that creates defects by generation of excessive electron–hole pairs causing electrical characteristics shifts. This study investigates the impact of gamma ray irradiation on dynamic characteristics of silicon and silicon carbide power MOSFET. The switching speed is limit at the higher doses due to the increase capacitance in power MOSFETs. Thus, the power circuit may operate improper due to the switching speed has changed by increasing or decreasing capacitances in power MOSFETs. These defects are obtained due to the penetration of Cobalt60 gamma ray dose level from 50krad to 600krad. The irradiated devices were evaluated through its shifts in the capacitance-voltage characteristics, results were analyzed and plotted for the both silicon and silicon carbide power MOSFET.